If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3n + -2 + 2n + 5 = 0 Reorder the terms: -2 + 5 + 3n + 2n = 0 Combine like terms: -2 + 5 = 3 3 + 3n + 2n = 0 Combine like terms: 3n + 2n = 5n 3 + 5n = 0 Solving 3 + 5n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 5n = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 5n = 0 + -3 5n = 0 + -3 Combine like terms: 0 + -3 = -3 5n = -3 Divide each side by '5'. n = -0.6 Simplifying n = -0.6
| 0=3b+27 | | a+2/a-1=a+11/a+4 | | b+12=-21 | | 1-2c-3c+100= | | 9y-8+4y= | | 3x/x^2 | | 9/540 | | ln(3x^2)-2x=0 | | 26+48x=-502 | | X=6-21 | | 10=n/6+9 | | -3(2t-2)+4t=7t-8 | | 6/174 | | 2/194 | | -0.5=-2x+8.1 | | 8/668 | | 18-33x=180 | | -3y-2y-y= | | 3/237 | | 3/261 | | 4a+5-a+2= | | 8z-z=-2+2z-1-2 | | 7/336 | | 9/603 | | 9t+5t-3t= | | 6/504 | | 28-4d=59-17 | | 7/322 | | 7/413 | | 7t+8(9t-1)=8(3t+9) | | 23-44x=199 | | 4/264 |